Interplay between superconductivity and magnetism in Cu-doped FeSe under pressure - Shylin, Sergii I.; Ksenofontov, Vadim; Naumov, Pavel G.; Medvedev, Sergey A.; Felser, Claudia (Journal of Superconductivity and Novel Magnetism, 2018)
Superconductivity in iron selenide is very sensitive to any dopants at levels of only a few percent. Here, we demonstrate how iron substitution by copper destroys superconductivity in FeSe, and argue why superconductivity reemerges under pressure. Detailed Mössbauer spectroscopy studies on 57 Fe-enriched Cu0.04 Fe0.97 Se reveal that at low temperatures part of the iron sites is magnetically ordered, and static magnetic moments destroy the superconducting pairing. Application of pressure leads to a collapse of the static magnetism and restoration of superconductivity with the maximal Tc value at pressure ∼ 8 GPa. The further pressure increase provokes a structural tetragonal-to-hexagonal phase transition and disappearance of superconductivity similarly to FeSe. The hyperfine parameters of the non-superconducting hexagonal phase of Cu0.04 Fe0.97 Se reveal a less covalent character of Fe–Se bonds and a noticeable higher value of the electric field gradient comparing to the tetragonal phase.
CRIS-Team Scopus Importer:2022-04-14
Keywords: High pressure; Iron selenide; Mössbauer spectroscopy; Superconductivity